2018
DOI: 10.1093/geronb/gby147
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations of Sensory and Cognitive Functioning: A Structural Equation Modeling Approach

Abstract: Objectives Although visual and hearing impairments have been found to be associated with cognitive decline in the old age, the mechanism underlying this relationship remains unclear. This study aimed at assessing the predictive role of visual and hearing difficulties on subsequent cognitive functioning. Method From the cohort of the first (2002) and fifth waves (2010) of the English Longitudinal Study of Ageing (ELSA), 3,508 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 46 publications
4
13
0
Order By: Relevance
“…Importantly, this suggests that associations between pure-tone hearing loss and brain structure are not confounded by group differences in their pure-tone hearing. A previous study reported that there was a higher prevalence of hearing loss (> 35 dB HL based on PTA of 500, 1000, 2000, and 4000 Hz in the better ear) in MCI compared to healthy older adults and in AD compared to MCI and healthy older adults (Quaranta et al, 2014); however, most studies do not have such data because they examine the association between pure-tone hearing loss and cognitive decline in healthy older adults or in a group who were initially healthy and at risk of developing dementia (de la Fuente et al, 2019; Deal et al, 2015, 2016, 2019; Okely et al, 2019; Osler et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, this suggests that associations between pure-tone hearing loss and brain structure are not confounded by group differences in their pure-tone hearing. A previous study reported that there was a higher prevalence of hearing loss (> 35 dB HL based on PTA of 500, 1000, 2000, and 4000 Hz in the better ear) in MCI compared to healthy older adults and in AD compared to MCI and healthy older adults (Quaranta et al, 2014); however, most studies do not have such data because they examine the association between pure-tone hearing loss and cognitive decline in healthy older adults or in a group who were initially healthy and at risk of developing dementia (de la Fuente et al, 2019; Deal et al, 2015, 2016, 2019; Okely et al, 2019; Osler et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Lindenberger & Baltes, 1994). Hearing loss (defined by pure-tone thresholds or measures of auditory processing such as speech-in-noise or word recognition tests) is related to self-reported (Curhan et al, 2019) and behavioral measures of cognitive decline in aging (de la Fuente et al, 2019; Fischer et al, 2016; Fortunato et al, 2016; Merten et al, 2019). Hearing loss also is linked to incident all-cause dementia (Albers et al, 2015; Deal et al, 2015, 2019; Gates et al, 2011; Lin, Metter, et al, 2011; Lin & Albert, 2014; Osler et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Processing speed was assessed with a letter cancellation test. Participants had to identify and cross out as many of two target letters as possible from a page that included random letters in rows and columns in one minute [10]. The total number of correctly crossed out letters provided the measure of processing speed.…”
Section: Processing Speed Assessmentmentioning
confidence: 99%
“…For many older adults such hearing problems often mean a reduced quality of life, social isolation, and higher rates of depressive symptoms (Arlinger, 2003;Ciorba et al, 2012;Pichora-Fuller et al, 2015;Vannson et al, 2015). Furthermore, hearing impairment in older adults is associated with cognitive decline (de la Fuente et al, 2019;Fischer et al, 2016;Fortunato et al, 2016;Merten et al, 2019) as well as a higher risk for incident all-cause dementia (Albers et al, 2015;Deal et al, 2019Deal et al, , 2015Gates et al, 2011;Lin et al, 2011;Lin and Albert, 2014;Osler et al, 2019).…”
Section: Introductionmentioning
confidence: 99%